KEMAMPUAN CUSTOMER SATISFACTION DALAM MEMEDIASI PENGARUH PERCEIVED VALUE DAN PERCEIVED SERVICE QUALITY TERHADAP REPURCHASE INTENTION (Studi Pada Pengguna Jasa Grab di Semarang) - Maskudi .; Sutopo .; Karsiati . (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2022)
ABSTRACTRepurchase intention is the customer's decision to repurchase goods or services that they have previously purchased from the company, including online transportation sectors. Repurchase intention is influenced by perceived value. In addition to perceived value, perceived service quality is also considered as one of the repurchase intention behavioral factors, where the higher the service quality perceived by the customer, the more likely the customer will repurchase. Satisfaction is considered as a strong indicator in encouraging customers to repurchase and in some cases it can moderate perceived value and perceived service quality to repurchase intention. However, there are still deviations regarding the role of customer satisfaction as intervening between perceived value and perceived service quality in transportation services such as Grab. Thus, there is still a need to study the effect of perceived value and perceived service quality on repurchase intention, as well as the influence of satisfaction in intervening those effects. This research is a causality study with a quantitative approach with a total of 146 respondents involved. The statistical analysis in this study used Structural Equation Model and Sobel Test. The results showed that perceived value and perceived service quality had a positive and significant effect on customer satisfaction. Perceived value and customer satisfaction also have a positive and significant effect on repurchase intention. Moreover, this study is able to prove that customer satisfaction plays a role as an intervening variable on the effect of perceived value and perceived service quality on repurchase intention of Grab service users in Semarang. Keyword : Custumor satisfaction, Percieved value, Percieved service quality, Repurchase intention ABSTRAKRepurchase intention adalah keputusan pelanggan untuk membeli ulang barang atau jasa yang pernah mereka beli sebelumnya dari perusahaan, termasuk sektor transportasi online. Repurchase intention dipengaruhi oleh perceived value. Selain perceived value, perceived service quality juga dianggap sebagai salah satu faktor perilaku repurchase intention, dimana semakin tinggi service quality yang dirasakan oleh pelanggan maka besar kemungkinan pelanggan akan kembali membeli produk dari perusahaan tersebut akan semakin tinggi. Kepuasan (satisfaction) dianggap sebagai indikator kuat dalam mendorong pelanggan untuk membeli ulang dan dalam beberapa penelitian dapat memoderasi perceived value dan perceived service quality terhadap repurchase intention. Akan tetapi, hingga saat ini masih terdapat kesenjangan mengenai hubungan variabel-variabel ini. Kajian mengenai pengaruh perceived value dan perceived service quality terhadap repurchase intention, serta besar pengaruh customer satisfaction dalam menjembataninya masih perlu dilakukan pada layanan transportasi online Grab. Penelitian termasuk dalam penelitian kausalitas dengan pendekatan kuantitatif yang melibatkan 146 responden. Analisis statistik dilakukan menggunakan Structural Equation Model (SEM) dan Sobel Test. Hasil penelitian menunjukkan perceived value dan perceived service quality berpengaruh positif signifikan terhadap customer satisfaction. Perceived value dan customer satisfaction juga berpengaruh positif signifikan terhadap repurchase intention. Terlebih lagi, penelitian ini mampu membuktikan bahwa customer satisfaction berperan sebagai variabel intervening pada pengaruh perceived value dan perceived service quality terhadap repurchase intention pada pengguna jasa Grab di Kota Semarang. Keyword : Custumor satisfaction, Percieved value, Percieved service quality, Repurchase intention